KEMAMPUAN FISKAL DAN PERTUMBUHAN EKONOMI DI KABUPATEN KONAWE UTARA - Sardi, Sardi (Pascasarjana Universitas Halu Oleo, 2016)
The purposes of the study were : 1) to find out the ability of financial, 2) economic growth, 3) relationship between financial ability and economic growth in North Konawe year 2009 – 2013. Data used in the study were primary and secondary data. Method of the study employeed descriptive analysis by using tools : 1) financial ability through ratio indicator of financial performance comprised of : degree of financial decentralizattion, independency of regional financial, appropriateness of regional expenses and financial dependence. 2) to find out the growth of economic through the value of PDRB ADHK, 2000, and 3) to find out the relationship between financial ability and economic growth using a) PAD performance analysis comprised of PAD share, PAD growth, and b) financial ability (IKK). Result of the study concluded that : 1) based on financial ability described that the ability of financial is low, this is shown by financial performance indicators, they are : decentralization of financial is very low, the independency of regional financial is low, the appropriateness of regional expenses to the total of regional expenses is not appropriate and the depedence to regional financial is high. 2) From the perspective of economic growth, in general, the growth of economic is rather good, with the everages of the growth is 8,05% per year. 3) the relationship between financial ability and economic growth is medium. This is shown by the indicator of PAD performance such as PAD share to medium expeses total. Higher PAD growth, elasticity of PAD to PDRB with the ratio of low elasticity. And the index of financial ability (IKK) is in the medium ability. Keywords : financial ability, economic growtth, PAD’s performance, index of financial ability.